Eradication of hepatitis C virus infection disclosing a previously hidden, underlying autoimmune hepatitis: Autoimmune hepatitis and HCV - Valentina Cacciato; Edoardo Casagrande; Giorgia Bodini; Manuele Furnari; Elisa Marabotto; Federica Grillo; Edoardo G. Giannini (Annals of Hepatology, 2020)
Chronic hepatitis C virus (HCV) infection and autoimmune disorders show a complex interplay, with HCV often being identified as the trigger of autoimmune phenomena or diseases. While there is evidence of successful HCV treatment with direct-acting antivirals (DAA) in patients with concomitant HCV and autoimmune hepatitis (AIH), there are also sparse reports of AIH developing during, or following, DAA treatment.Here we report a case of a patient with suspected concomitant HCV and AIH who underwent liver biopsy but showed no histological hallmarks of autoimmunity. The patient later developed a hepatitic flare following DAA-induced viral clearance, and a second liver biopsy showed features compatible with AIH. Response to corticosteroid and azathioprine treatment was seen. This reports demonstrates that patients with features of auto-reactivity and HCV after DAA-induced viral clearance require careful follow-up.